Artificial Intelligence (AI) in the Banking Industry: A Review of Service Areas and Customer Service Journeys in Emerging Economies - Tajudeen Alaburo Abdulsalam; Rofiat Bolanle Tajudeen (Business & Management Compass)
The banking industry's shift towards digitalization, particularly Web 2.0 banking, signifies a profound change in the bank-client relationship. This transformation integrates digital elements into consumers' lives, digitising everyday activities and highlighting the importance of online social platforms and digital business operations. AI's growing interest in academia and commerce underscores its significant role in customer service. The study examines AI strategies in the banking industry, focusing on service areas and adaptation to the evolving technological landscape, particularly in customer service in developing economies. By adopting an interpretivist philosophy emphasising practicality, a qualitative approach was employed through a systematic literature review of 90 articles using thematic analysis. The research highlights AI's growing use in process automation, customer experience, stock market trend prediction, credit risk management, online banking, marketing management, and auditing. It concludes AI's positive impact on banking operational efficiency and customer service by recommending ethical AI usage, stakeholder collaboration, trust in data handling, and robust internal control systems. Additionally, it suggests exploring the association between organisational culture, leadership, and AI integration in developing economies. The research contributes to the theoretical and empirical frameworks that explain how AI is optimally integrated into banking operations, guiding policymakers and practitioners in leveraging AI to foster financial inclusion and economic growth. Future researchers should include non-profit institutions and non-financial performance metrics to gain insights into AI’s sustainability implications in banks beyond financial metrics.